A monastic renaissance at St. Albans : Thomas Walsingham and his circle, c. 1350-1440 - Clark, James G. (Clarendon Press ; Oxford University Press, 2004)
A Monastic Renaissance at St Albans is a study of intellectual life - teaching, preaching, the production of books, and the pursuit of scholarship - at one of England's greatest monasteries at the end of the Middle Ages. It has always been assumed that the monasteries fell into decline long before the Dissolution, but this study demonstrates the continuing vitality of education and learning in English cloisters and even uncovers evidence of a revival in Classical studies comparable to the continental Renaissance. - ;A Monastic Renaissance at St Albans is a study of intellectual life at the abb.